2019
DOI: 10.1002/gcc.22737
|View full text |Cite
|
Sign up to set email alerts
|

Novel TG‐FGFR1 and TRIM33‐NTRK1 transcript fusions in papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is most common among all thyroid cancers. Multiple genomic alterations occur in PTC, and gene rearrangements are one of them. Here we screened 14 tumors for novel fusion transcripts by RNA‐Seq. Two samples harboring RET/PTC1 and RET/PTC3 rearrangements were positive controls whereas the remaining ones were negative regarding the common PTC alterations. We used Sanger sequencing to validate potential fusions. We detected 2 novel pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Molecular markers, such as the BRAF V600E mutation or the TERT mutation, have been well studied in large cohorts, and the management of thyroid nodules harboring these mutations has also been recommended in the American and the European Thyroid Association Guidelines [ 18 , 19 ]. However, data on NTRK fusion genes in TC are very limited due to their rare occurrence, and therefore there are only small cohorts of NTRK fusion-positive samples that are described and characterized [ 10 , 11 , 12 , 15 , 20 , 21 , 22 , 23 , 24 ]. Another reason is their more expensive and challenging accurate testing requiring RNA of suitable quality.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers, such as the BRAF V600E mutation or the TERT mutation, have been well studied in large cohorts, and the management of thyroid nodules harboring these mutations has also been recommended in the American and the European Thyroid Association Guidelines [ 18 , 19 ]. However, data on NTRK fusion genes in TC are very limited due to their rare occurrence, and therefore there are only small cohorts of NTRK fusion-positive samples that are described and characterized [ 10 , 11 , 12 , 15 , 20 , 21 , 22 , 23 , 24 ]. Another reason is their more expensive and challenging accurate testing requiring RNA of suitable quality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study reported a patient with ETV6‐NTRK secretory thyroid carcinoma who had a long‐lasting response (21 months) to larotrectinib with complete resolution of the radiologically detectable tumor, and a patient with TPR‐NTRK1 PTC who had a 33% decrease in tumor burden and stable disease for 15 months 34 . NTRK gene fusions occur relatively frequently in thyroid cancer—in 2‐15% of adult patients, with the highest levels observed in post‐Chernobyl reactor accident cases, and in 2‐26% of pediatric patients with thyroid cancer 34‐40 . A number of NTRK gene rearrangements have been observed in thyroid carcinomas, including ETV6‐NTRK3 , TPR‐NTRK1 , RBPMS‐NTRK3 , SQSTM1‐NTRK1/3 , and EML4‐NTRK3 34 .…”
Section: Discussionmentioning
confidence: 99%
“…34 NTRK gene fusions occur relatively frequently in thyroid cancer-in 2-15% of adult patients, with the highest levels observed in post-Chernobyl reactor accident cases, and in 2-26% of pediatric patients with thyroid cancer. [34][35][36][37][38][39][40] A number of NTRK gene rearrangements have been observed in thyroid carcinomas, including ETV6-NTRK3, TPR-NTRK1, 34 As demonstrated in this case, NTRK-rearranged thyroid cancer is clinically aggressive with a high rate of metastatic spread, but with low mortality when treated with TRK inhibitor therapy. 34 Due to the prevalence and actionability of NTRK gene fusions, upfront molecular testing should be recommended for patients with advanced or metastatic RAI-R DTC, if feasible.…”
Section: F-fdg 2-deoxy-2-[fluorine-18] Fluoro-d-glucose; Pet/ct Positron Emission Tomography/computed Tomographymentioning
confidence: 92%
“…5,6 Recently, published literature increasingly suggested that somatic mutations in BRAF, HRAS, KRAS, NRAS, TERT, RET, PIK3CA, PTEN, TP53, CTNNB1,AKT1, GNAS, PAX8/PPARγ, NTRK1, and TSHR genes have been associated with diagnosis and treatment of TC. [7][8][9][10][11][12][13][14][15][16] Next generation sequencing (NGS) is a newlydeveloped technique offered a cost-effective approach for detecting multiple genetic alterations and provided quantitative assessment of mutation frequency. 17,18 Therefore, a panel designed to these 15 target genes was used to detect molecular alterations by NGS in PTC.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, single gene assays, such as BRAF V600E mutation, have been commonly used for finding molecular alterations by Sanger sequence, immunohistochemistry, and real time PCR in PTC 5,6 . Recently, published literature increasingly suggested that somatic mutations in BRAF, HRAS, KRAS, NRAS, TERT, RET, PIK3CA, PTEN, TP53, CTNNB1,AKT1, GNAS, PAX8/PPARγ, NTRK1, and TSHR genes have been associated with diagnosis and treatment of TC 7‐16 . Next generation sequencing (NGS) is a newly‐developed technique offered a cost‐effective approach for detecting multiple genetic alterations and provided quantitative assessment of mutation frequency 17,18 .…”
Section: Introductionmentioning
confidence: 99%